2019
DOI: 10.1073/pnas.1821065116
|View full text |Cite
|
Sign up to set email alerts
|

Organic–mineral interfacial chemistry drives heterogeneous nucleation of Sr-rich (Ba x , Sr 1− x )SO 4 from undersaturated solution

Abstract: Sr-bearing marine barite [(Ba x , Sr 1−x )SO 4 ] cycling has been widely used to reconstruct geochemical evolutions of paleoenvironments. However, an understanding of barite precipitation in the ocean, which is globally undersaturated with respect to barite, is missing. Moreover, the reason for the occurrence of higher Sr content in marine barites than expected for classical crystal growth processes remains unknown. Field data analyses suggested that organic molecules may regulate the formation and composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Unfortunately, experimental difficulties (2) and contradictory theoretical results (14,15) have thus far preempted an accurate assessment of miscibility in the barite-celestite series. Consistent with expectations, Deng et al (6) observed almost no strontium substitution in their homogeneous crystallization experiments. However, the results of their heterogeneous crystallization experiments were quite unexpected: They found that the compositions of the barite grains that formed in association with the organic film were substantially altered, with 20 to 99% of their barium content replaced by strontium.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…Unfortunately, experimental difficulties (2) and contradictory theoretical results (14,15) have thus far preempted an accurate assessment of miscibility in the barite-celestite series. Consistent with expectations, Deng et al (6) observed almost no strontium substitution in their homogeneous crystallization experiments. However, the results of their heterogeneous crystallization experiments were quite unexpected: They found that the compositions of the barite grains that formed in association with the organic film were substantially altered, with 20 to 99% of their barium content replaced by strontium.…”
supporting
confidence: 74%
“…However, the results of their heterogeneous crystallization experiments were quite unexpected: They found that the compositions of the barite grains that formed in association with the organic film were substantially altered, with 20 to 99% of their barium content replaced by strontium. Through a particularly apt usage of a kinetic model of solidsolution nucleation previously developed by Pina and Putnis (16), Deng et al (6) show that the strontium enrichment they observed in the heterogeneous precipitates is consistent with a transition from a growth-dominated regime in the bulk fluid to a nucleation-dominated regime at the organic interface.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…This observation is not surprising considering that our system is heterogeneous due to the presence of minerals and HS. In fact, multiple studies have shown mineral nucleation and growth in under-saturated bulk solutions if organic materials and solid interfaces serve as nucleation templates to locally enrich ions (Deng et al, 2019;Hövelmann et al, 2018;Roberts et al, 2004). For example, Deng et al (2019) showed barite formation on organic films, despite their bulk solution was under-saturated with respect to barite, likely because of local super-saturation near the organic molecules.…”
Section: Secondary Mineralizationmentioning
confidence: 99%